A study on the use of water as a medium for the thermal inactivation of endogenous lipase in oil of palm fruit - Shehu, Umar Etsu; Mokhtar, Mohd Noriznan; Mohd Nor, Mohd Zuhair; Samsu Baharuddin, Azhari; Mat Nawi, Nazmi (MDPI, 2019)
The heat treatment of oil palm fruit using saturated steam (413 K) in conventional oil palm processing has been reported to be ineffective in terms of heat distribution and penetration into the fruit bunch inner layer; hence, there is a desire to explore other alternative processes. In this study, oil palm fruit was treated in water at temperatures between 308 K and 343 K. The effects of the treatment on the in vivo activity of the lipase, the abscission layer of the fruit, and the integrity of the oil globule membrane were observed. The results showed in vivo residual lipase activity to be almost completely inactivated after 40 min of heat treatment at 343 K. The micrograph of the fruit mesocarp exhibited disintegration of the oil globule membrane as well as dissolution of the pectin layer architecture of the abscission zone after the treatment at this temperature. A dynamic mathematical modeling of heat transfer was employed, and coupled with reaction kinetics of lipase inactivation. The inactivation kinetics was found to be a non-elementary reaction, and the initial rate constant, k0dec, and activation energy, Edec, of the reaction were estimated to be 0.035 U−0.85/kg-mes−0.85⋅min and 153,052 kJ/kmol, respectively. The findings suggested the viability of water as a medium of heat treatment instead of the conventional steam treatment in oil palm processing.